2022
DOI: 10.1111/jeb.14023
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs in defence to pathogen species revealed in expanding nematode populations

Abstract: Hosts have evolved a variety of defence strategies due to the negative impacts of pathogens on host fitness. Hosts can avoid pathogens, limit their within-host growth (i.e. resistance) and/or limit their damage (i.e. tolerance) (Rivas et al., 2014). Within these broad defence categories, host responses to pathogens can vary from general to specific through a variety of recognition mechanisms, behaviours, signalling pathways and effector molecules (reviewed in Medzhitov & Janeway, 1997). Pathogen exposures over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Investment in life-history traits that improve reproduction and offspring survival is associated with a reduction in defense efficiency in C. elegans . This result was consistent with numerous studies demonstrating negative relationship between reproduction and immunity efficiency in birds [ 63 ], insects [ 17 ], gastropods [ 25 ] or the nematode C. elegans [ 64 , 65 ]. Furthermore, studies have demonstrated in C. elegans and D. melanogaster that the absence of reproduction linked to the lack of a germline increases resistance to various pathogens [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…Investment in life-history traits that improve reproduction and offspring survival is associated with a reduction in defense efficiency in C. elegans . This result was consistent with numerous studies demonstrating negative relationship between reproduction and immunity efficiency in birds [ 63 ], insects [ 17 ], gastropods [ 25 ] or the nematode C. elegans [ 64 , 65 ]. Furthermore, studies have demonstrated in C. elegans and D. melanogaster that the absence of reproduction linked to the lack of a germline increases resistance to various pathogens [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 92%